2017
DOI: 10.1016/j.nlm.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Sensory system development influences the ontogeny of hippocampal associative coding and trace eyeblink conditioning

Abstract: Until recently, it was believed that hippocampal development was the primary rate-limiting factor in the developmental emergence of hippocampal forms of learning, such as trace eyeblink conditioning (EBC). Indeed, hippocampal neuronal activity shows an age-related increase in both complexity and task responsiveness during trace EBC. However, recent work from our laboratory suggests that sensory system development may also play a role. Training with the earlier-developing somatosensory system results in an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(50 reference statements)
1
0
0
Order By: Relevance
“…For example, a reduction in the hippocampal neurogenesis of rats has been found to coincide with impaired learning on a hippocampal‐dependent trace EBC task (Shors, Townsend, Zhao, Kozorovitskiy, & Gould, ; Winocur, Wojtowicz, Sekeres, Snyder, & Wang, ). Furthermore, consistent with findings on neuronal activation in the hippocampus of rats during trace EBC (Goldsberry, Kim, & Freeman, ; Plakke, Freeman, & Poremba, ), a functional neuroimaging study with human adults found that the right medial temporal lobe, including the hippocampus, was significantly activated during trace conditioning relative to a non‐hippocampal‐dependent EBC paradigm (Cheng et al, ). Thus, if EBC engages the right rather than left hippocampus, then it may have more underlying neural circuitry in common with spatial reorientation than episodic memory.…”
Section: Introductionsupporting
confidence: 81%
“…For example, a reduction in the hippocampal neurogenesis of rats has been found to coincide with impaired learning on a hippocampal‐dependent trace EBC task (Shors, Townsend, Zhao, Kozorovitskiy, & Gould, ; Winocur, Wojtowicz, Sekeres, Snyder, & Wang, ). Furthermore, consistent with findings on neuronal activation in the hippocampus of rats during trace EBC (Goldsberry, Kim, & Freeman, ; Plakke, Freeman, & Poremba, ), a functional neuroimaging study with human adults found that the right medial temporal lobe, including the hippocampus, was significantly activated during trace conditioning relative to a non‐hippocampal‐dependent EBC paradigm (Cheng et al, ). Thus, if EBC engages the right rather than left hippocampus, then it may have more underlying neural circuitry in common with spatial reorientation than episodic memory.…”
Section: Introductionsupporting
confidence: 81%